MATHEMATICAL MODELS FOR COVID-19: A REVIEW ANALYSIS - Mahajan, Shveta (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In the past century, the COVID-19 epidemic has caused a global health disaster never seen before. With its ever-expanding influence on the economy, society, and health, it is destined to rank among the worst worldwide calamities since the World Wars and the 1918 epidemic. This novel illness mostly spreads through human carriers, and it does so far more quickly than other flu viruses and coronaviruses that have previously been discovered. It will be difficult to eradicate this illness even with the development and distribution of vaccinations. It is critical to comprehend the virus's mode of transfer from one host to another as well as how future infection hotspots can be identified in order to save lives. A significant part in the ongoing dilemma has been played by mathematical models, which have influenced state policies and many of the global social distancing initiatives. In this paper, we summarize some of the key mathematical models that underpin the continuous preparation and reaction activities. These models vary in terms of their application, mathematical structure, and range.